The accidental favorite : a novel - Littlewood, Fran (Henry Holt and Company, 2025)
"From the New York Times bestselling author of Amazing Grace Adams comes a wryly resonant and deeply moving family dramedy investigating the question so many of us have asked ourselves: do my parents have a favorite? Vivienne and Patrick Fisher have done an excellent job raising their three daughters, Alex, Nancy, and Eva. They're well-adjusted women with impressive careers, caring partners, exciting hobbies, and sweet children. So it's with great anticipation that three generations of Fishers gather at a beautiful glass house in the English countryside for a weeklong celebration of Vivienne's seventieth birthday. But when Patrick's reaction to a freak accident on the first day of the trip inadvertently reveals that he has a favorite daughter, no one is prepared for the shockwaves it sends through the family. Decades-old unresolved sibling rivalries are suddenly unmasked. And be it newly uncovered smoking habits, ancient crushes, or private doubts about life decisions both big and small, no one's secrets are safe. Still-tender wounds are reopened amid an audience of friends, husbands, grandchildren, and even coworkers, and as the family's past is re-written, they find themselves suddenly unmoored. In a lively, poignant examination of memory, sisterhood, and family ties, Fran Littlewood reminds us just why it is that people in glass houses shouldn't throw stones"--